The effectiveness of free-recall, cognitive instruction and closed-ended questions when students with and without disabilities provide eyewitness reports of another’s transgression - Wyman, Joshua (Psychology, crime & law, 2021)
The current study evaluated the efficacy of free-recall, cognitive instruction and closed-ended questions with students (N = 50; ages 6–18) with developmental disabilities. After watching a magic show wherein the magician made a major error, the students were asked by the magician to keep the transgression a secret. Next, students were interviewed using the Cognitive Interview (CI: free-recall, cognitive instruction and closed-ended questions) or a Standard Interview (SI: free-recall and closed-ended questions) by an unfamiliar researcher whereby their statement quality (statement consistency, veracity and disclosure forthcomingness) and quantity (number of words, transgression details and events recalled) were evaluated. The CI group disclosed significantly more total words and events than the SI group, without compromising testimony consistency; while not significant, descriptive differences in transgression details were found between interview groups. Nevertheless, there were no significant interview group differences in disclosure honesty or forthcomingness. Truth-tellers provided the most forthcoming and detailed statements on the free-recall question, irrespective of interview type. Conversely, lie-tellers rarely discussed the alleged transgression, and primarily lied on the final direct closed-ended question. These results suggest that the CI can be effective with students with developmental disabilities for increasing eyewitness memory recall.